Step 1: move all terms to one side
7 + 2x^2 - 10x = 0
Step 2: Use the quadratic formula
X = 10 + 2(square root of 11). 10-2 _/—-11
————————————. ——————
4. , 4
Step 3: Simplify solutions
X= 5 + (square root of 11) 5 - (square root 11)
——————————- , ————————
2. 2
Line 4. 12 would be divided by 6, not multiplied.
We have that
the correct expression is
y=2<span>^</span>(x+3)
using a graph tool
see the attached figure
the answer is the option C
Answer:
dude wheres the choices
Step-by-step explanation:
True, this is a Pythagorean identity.